Preparation, Characterisation And Properties Of Uscovite/Acrylonitrile Utadiene Styrene Nanocomposites - Che Ismail, Nor Hafizah (2020)
The development of acrylonitrile butadiene styrene (ABS) nanocomposite based on non-expandable clay minerals presents a promising approach that has been relatively unexplored. Muscovite was chosen over the most commonly used clay minerals, due to its higher aspect ratio when compared to montmorillonite (MMT). As such, this study investigated the possibilities of muscovite to expand and to function as reinforcement filler in ABS matrix via two-stage ion exchange process for fillermatrix compatibilisation and melt compounding for polymer fabrication. The modification process involved treatment with LiNO3 (first-stage) and modification with cetyltrimethylammonium bromide (CTAB) at various concentrations as a secondstage cation exchange reaction. Characterisation of treated muscovite was assessed by using X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier transform infrared (FTIR), Brunauer–Emmett–Teller (BET), Field emission scanning electron microscopy (FESEM) coupled with Energy dispersive x-ray spectroscopy (EDX), and Transmission Electron Microscopy (TEM). The experimental outcomes showed that not only basal spacing, but also specific surface area increased while the number of stacked individual silicate layers of organoclay kept decreasing at high CTAB concentrations, which signified separation within the muscovite layers. The changes in basal spacing further evidenced that muscovite displayed a possibility for expansion. A further goal of this research is to extend the application of organomuscovite (OM) filled ABS matrix. In this case, OM and unmodified muscovite were embedded in ABS matrix at various filler loading of 1, 3, and 5 wt.%. The aspects addressed included the effect of ion-exchange process, the degree of dispersion that was achieved, and the effect of various filler loading on the mechanical properties of ABS nanocomposites. Along this line, this study reveals that the ABS/OM nanocomposites possessed a tendency to exemplify enhanced mechanical properties, in comparison to those of ABS/muscovite. Nevertheless, incorporation of muscovite at all filler loadings led to a slight reduction in tensile strength, a significant decrease in elongation at break, a slight improvement in modulus and hardness, and increment in thermal stability over those of the neat ABS. Flexural strength and modulus were improved by 10% and 28%, respectively, when compared to those retrieved from neat ABS. Both wide angle x-ray diffraction (WAXD) and TEM analyses indicated the formation of mixed intercalated and exfoliated structures with incorporation of OM. Therefore, the development of non-expandable muscovite incorporated with polymer matrices provide the opportunities to explore new functionalities beyond those found in conventional materials.